USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES FOR THE EXPORT OF ECONOMIC SUBJECTS OF SAMARKAND REGION - Rustamov, Zafar Xudoykulovich (Educational Research in Universal Sciences, 2023)
This article is aimed at improving the use of information and communication technologies to support the export of entrepreneurship, covering the processes of further expansion of business activity and creating conditions for domestic producers, including their export to foreign markets and exports.